Hindu pluralism : religion and the public sphere in early modern South India - Fisher, Elaine M., 1984- (South Asia across the disciplines., 2017)
"Much has been written about the historical origins of the unity of Hinduism. Hindu difference has been read through the lens of the term "sectarianism," a concept that translates devotion as dissent, and community as a potential precursor to communalism. In Hindu Pluralism, Elaine. M. Fisher argues that it is the plurality of Hindu religious identities, and their embodiment and contestation in public space, that first reveals the emergence of Hinduism as a unified religion in south India and an integral feature of a distinctively Indic early modernity prior to British Colonialism."--Provided by publisher